Theoretical studies on the two-photon absorption of II–VI semiconductor nano clusters - Deyang Yu; YangYang Hu; Guiling Zhang; Weiqi Li; Yongyuan Jiang (Scientific Reports, 2022)
Abstract Semiconductor clusters, ZnnOn, ZnnSn, and CdnSn (n = 2–8), were optimized and the corresponding stable structures were acquired. The symmetry, bond length, bond angle, and energy gap between HOMO and LUMO were analyzed. According to reasonable calculation and comparative analysis for small clusters Zn2O2, Zn2S2, and Cd2S2, an effective method based on density function theory (DFT) and basis set which lay the foundation for the calculation of the large clusters have been obtained. The two-photon absorption (TPA) results show that for the nano clusters with planar configuration, sizes play important role on the TPA cross section, while symmetries determine the TPA cross section under circumstance of 3D stable structures. All our conclusions provide theoretical support for the development of related experiments.